2012
DOI: 10.4088/jcp.11m07164
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-Compulsive Symptoms in Patients With Schizophrenia

Abstract: Treatment with clozapine in patients with schizophrenia is associated with a higher prevalence of OCS, especially when patients have been taking clozapine for 6 months or longer. We cannot rule out the possibility that this association is related to illness characteristics. Patients treated with risperidone or olanzapine or without treatment with antipsychotic medication had comparable prevalence of OCS, all significantly higher than the control sample.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Length of clozapine treatment is a replicated risk factor for developing OCD (Lin et al 2006 ; Boyette et al 2011 ; Schirmbeck et al 2011 ; Scheltema Beduin et al 2012 ). However, the evidence for OCD being a clozapine dose-dependent side effect is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Length of clozapine treatment is a replicated risk factor for developing OCD (Lin et al 2006 ; Boyette et al 2011 ; Schirmbeck et al 2011 ; Scheltema Beduin et al 2012 ). However, the evidence for OCD being a clozapine dose-dependent side effect is still inconclusive.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors suggested that in these cases OCS might be considered an adverse event of SGA and introduced the term “antipsychotic-induced OCS” or “secondary OCS” (s-OCS)[5,10]. Nevertheless, because sometimes OCS occur or worsen also under no treatment or treatment with first-generation antipsychotics which are not primarily 5HT2-R-antagonistic[11], an interaction between genetic/biological predispositions, psychosocial factors and treatments could better explain the phenomenon[12]. …”
Section: Introductionmentioning
confidence: 99%
“…Clozapine is not recommended for OCD based on one small open-label trial that failed to demonstrate benefit [ 19 ]. Additionally, clozapine has been described to induce or worsen OCS/OCD in mostly small studies and case reports involving patients with a primary psychotic disorder [ 5 , 20 , 21 ]. In psychotic illnesses, clozapine-induced OCS should not be a reason for discontinuation when clear benefits for decreasing psychosis occur.…”
Section: Discussionmentioning
confidence: 99%